Biochemical Characterization of Prostate-Specific Membrane Antigen From Canine Prostate Carcinoma Cells - Wu, Lisa Y. (Prostate, 2014)
BACKGROUND: Prostate-specific membrane antigen (PSMA) remains an important target for diagnostic and therapeutic application for human prostate cancer. Model cell lines have been recently developed to study canine prostate cancer but their PSMA expression and enzymatic activity have not been elucidated. The present study was focused on determining PSMA expression in these model canine cell lines and the use of fluorescent small-molecule enzyme inhibitors to detect canine PSMA expression by flow cytometry. METHODS: Western blot and RT-PCR were used to determine the transcriptional and translational expression of PSMA on the canine cell lines Leo and Ace-1. An endpoint HPLC-based assay was used to monitor the enzymatic activity of canine PSMA and the potency of enzyme inhibitors. Flow cytometry was used to detect the PSMA expressed on Leo and Ace-1 cells using a fluorescently tagged PSMA enzyme inhibitor. RESULTS: Canine PSMA expression on the Leo cell line was confirmed by Western blot and RT-PCR, the enzyme activity, and flow cytometry. Kinetic parameters K(m) and V(max) of PSMA enzymatic activity for the synthetic substrate (PABGgG) were determined to be 393 nM and 220 pmol min (−1) mg protein (−1), respectively. The inhibitor core 1 and fluorescent inhibitor 2 were found to be potent reversible inhibitors (IC(50) = 13.2 and 1.6 nM, respectively) of PSMA expressed on the Leo cell line. Fluorescent labeling of Leo cells demonstrated that the fluorescent PSMA inhibitor 2 can be used for the detection of PSMA-positive canine prostate tumor cells. Expression of PSMA on Ace-1 was low and not detectable by flow cytometry. CONCLUSIONS: The results described herein have demonstrated that PSMA is expressed on canine prostate tumor cells and exhibits similar enzymatic characteristics as human PSMA. The findings show that the small molecule enzyme inhibitors currently being studied for use in diagnosis and therapy of human prostate cancer can also be extended to include canine prostate cancer. Importantly, the findings demonstrate that the potential of the inhibitors for use in diagnosis and therapy can be evaluated in an immunocompetent animal model that naturally develops prostate cancer before use in humans.